Psychological work in humanitarian emergencies in Haiti and Democratic Republic of Congo: some considerations based on two work experiences - Weintraub, Ana Cecilia Andrade de Moraes (Saúde e Sociedade, 2011)
Through the description of two examples of psychological interventions in humanitarian emergencies, this article aims to problematize the work of the psychologist in those situations. The concepts of "humanitarianism" and "emergency" are discussed based on two interventions made in Haiti and in the Democratic Republic of Congo. In both countries the mental health interventions happened inside a humanitarian organization and the objective of those interventions was to offer psychosocial support to the population of concern through a national mental health team. Cultural specificities, as well as theoretical and methodological challenges to the work of the psychologist in those situations are presented, especially those related to moral issues, to gender-based conflicts and to the insertion of the psychological work in a context where there is very little institutional support. Considerations related to theories and techniques of the area are presented, emphasizing the importance of interpreting the contents of the discourses taking into account the culture from where each person comes.